Effective pursuit strategies based on the use of the Lyapunov function - Pashko, S. V. (Reports of the National Academy of Sciences of Ukraine, 2016)
This paper is concerned with differential pursuit-evasion games, in which several players chase one. The time of capture of a target is used as the criterion. It is assumed that the target is surrounded by pursuers. The function that sets the exact guaranteed time of a capture of the target for the well-known strategy of parallel approach is described. This function is used as a Lyapunov function for constructing the new chase strategy, which outperforms the strategy of parallel approach.